2005
DOI: 10.1002/ana.20523
|View full text |Cite
|
Sign up to set email alerts
|

CINRG randomized controlled trial of creatine and glutamine in Duchenne muscular dystrophy

Abstract: We tested the efficacy and safety of glutamine (0.6 gm/kg/day) and creatine (5 gm/day) in 50 ambulant boys with Duchenne muscular dystrophy in a 6-month, double-blind, placebo-controlled clinical trial. Drug efficacy was tested by measuring muscle strength manually (34 muscle groups) and quantitatively (10 muscle groups). Timed functional tests, functional parameters, and pulmonary function tests were secondary outcome measures. Although there was no statistically significant effect of either therapy based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 8 publications
1
55
0
2
Order By: Relevance
“…[3][4][5] Corticosteroid treatment for DMD 6-12 is recommended by an American Academy of Neurology practice parameter.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Corticosteroid treatment for DMD 6-12 is recommended by an American Academy of Neurology practice parameter.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…[3][4][5] Corticosteroid treatment for DMD [6][7][8][9][10][11][12] is recommended by an American Academy of Neurology practice parameter. 13 Furthermore, a recently published standard of care review emphasized the benefit of corticosteroids for DMD.…”
mentioning
confidence: 99%
“…The other study evaluated creatine to glutamine and placebo in steroid-naĂŻve boys with DMD in a 6-month, double-blinded trial. 4 Supplementation with glutamine is felt to prevent muscle catabolism. This study found no statistically significant effect of either therapy on manual and quantitative muscle strength, although there appeared to be a trend towards less deterioration in all other outcome measures.…”
Section: Supplementsmentioning
confidence: 99%
“…2 Other researchers have reported a good correlation between strength and function in patients with spinal muscular atrophy. 3 Studies have been further confounded due to the question of correlations between age and strength 4 and age and function.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other researchers have reported a good correlation between strength and function in patients with spinal muscular atrophy. 3 Studies have been further confounded due to the question of correlations between age and strength 4 and age and function. 1 …”
Section: Introductionmentioning
confidence: 99%